New Carbon Based Materials for Electrochemical Energy Storage Systems: Batteries, Supercapacitors and Fuel Cells - Barsukov, Igor V.; Barsukov, Igor V.; Johnson, Christopher S.; Johnson, Christopher S.; Doninger, Joseph E.; Doninger, Joseph E.; Barsukov, Vyacheslav Z.; Barsukov, Vyacheslav Z. (Nato Science Series II:, Mathematics, Physics and Chemistry,, 2006)
Carbonaceous materials play a fundamental role in electrochemical energy storage systems. Carbon in the structural form of graphite is widely used as the active material in lithium-ion batteries; it is abundant, and environmentally friendly. Carbon is also used to conduct and distribute charge effectively throughout composite electrodes of supercapacitors, batteries and fuel cells. The electronic conductive pathways are critical to delivering and extracting current out of the device. However, many challenges and the understanding of the role of carbon and its stability and efficiency in charge storage applications still exists. This NATO-ARW volume contains a diverse collection of papers addressing the role of carbon in some key electrochemical systems, both conventional and emerging. These papers discuss the latest issues associated with development, synthesis, characterization and use of new advanced carbonaceous materials for electrochemical energy storage. Such systems include: metal-air primary and rechargeable batteries, fuel cells, supercapacitors, cathodes and anodes of lithium-ion and lithium polymer rechargeable batteries, as well as nanocarbon materials of the future.